Subjective Cognitive Decline in the Elderly: Concept, Diagnosis, Status, and Influencing Factors - Yongmei, Hou (Disease and Health: Research Developments Vol. 7, 2025)
Background: Subjective cognitive decline (SCD) may precede mild cognitive impairment (MCI), and its diagnosis and intervention play a significant role in promoting the prevention and treatment of Alzheimer's disease. Objective: To review the evolution of the SCD concept, diagnostic approaches, prevalence rates, and key influencing factors. Methods: Using literature retrieval, with "subjective cognitive decline+the elderly" "subjective cognitive decline+elder people" or "subjective cognitive decline+old people" as the keywords, empirical papers published in English or Chinese in the past 20 years were reviewed from Google Scholar, Pubmed, CNKI, and Wanfang Database. Results: Sixty articles were included. Previous studies have shown that the definition of SCD has undergone four stages over 43 years, with gradually evolving definitions and criteria over time. The diagnosis of SCD includes assessment with scales and laboratory testing, but there is a lack of standardized diagnostic procedures and gold standards for testing. The prevalence of SCD in the elderly ranges from 17.4% to 80.0%, with significant regional differences. The influencing factors of SCD in the elderly involve multiple levels and dimensions, including demographic variables, psychological factors, social factors, and biomedical factors. Conclusion: SCD is common among the elderly and can greatly hinder their physical and mental health as well as quality of life. Future research should focus on developing standardized diagnostic criteria, establishing universally accepted testing methods, and conducting large-scale longitudinal and cross-cultural studies to better understand the trajectory of SCD.